2018
DOI: 10.1049/iet-pel.2018.5037
|View full text |Cite
|
Sign up to set email alerts
|

Modified voltage‐mode controller for the quadratic boost converter with improved output performance

Abstract: The control of the quadratic boost converter with unknown load resistance and where only the output voltage is used for feedback purposes is addressed. In the existing voltage-mode controlled converter system, there exists a performance 'trade-off' between the transient responses after the onset of a reference input and a load disturbance due to the usage of the traditional proportional-integral control scheme. To overcome these problems, a modified voltage-mode controller is proposed. The proposed controller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
6
0
2
Order By: Relevance
“…From the equilibrium point described in (6)–(8), it can be observed that the proposed converters have the same current through inductors compared with converters in Fig. 1 [8–15], but capacitors are charged at different voltage levels. Table 1 shows a comparison of voltage in capacitors.…”
Section: Proposed Convertermentioning
confidence: 99%
See 2 more Smart Citations
“…From the equilibrium point described in (6)–(8), it can be observed that the proposed converters have the same current through inductors compared with converters in Fig. 1 [8–15], but capacitors are charged at different voltage levels. Table 1 shows a comparison of voltage in capacitors.…”
Section: Proposed Convertermentioning
confidence: 99%
“…Other plausible solutions may be found based on magnetic coupling [6,7]. Another alternative is the use of quadratic gain converters [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve the minimum size of L 2 , a similar analysis should be done. The only difference is in their average current equations ( 14and (19)). Thus, the equation of L 2 min is…”
Section: Minimum Inductance Of the Inductorsmentioning
confidence: 99%
“…The methods include switched-inductor and switched capacitor techniques to increase the voltage gain of different converters [4,[13][14][15]. In addition, using interleaved configuration causes high-voltage gain and reduction of voltage stress [16][17][18][19]. Although the methods have advantages, they are costly and bulky and that encourage researchers to present new converters with novel configurations.…”
Section: Introductionmentioning
confidence: 99%